Pengaruh Ukuran Perusahaan, Kualitas Audit, Kepemilikan Keluarga, Struktur Kepemilikan Terkonsentrasi Dan Return On Assets (Roa) Terhadap Manajemen Laba Akrual (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Indeks LQ45 Bursa Efek Indonesia periode 2011-2015 ) - KHOTIMAH, LAILLATUL; , Dra. Rina Trisnawati, M.Si, Akt.Ph.D (2017)
The purpose of this study is to examine the effect of firm size, quality audits, family ownership, concentrated structure ownership and return on assets (ROA) to earnings management which calculated using discretionary accruals with a modified Jones models. The sample used in this research is manufacturing companies listed in index LQ45 Indonesia Stock Exchange during 2011-2015 period. The sample of this study use purposive sampling methods and obtained 121 manufacturing companies. By using multiple regression analysis, the results that the firm size, quality audit and concentrated ownership structure has no effect on earnings management, while family ownership and return on assets (ROA) have effect on earnings management.